Problematyka edukacji dziewcząt na łamach czasopism kobiecych w latach 1918-1939 - Łozowska-Marcinkowska, Kamilla (Biuletyn Historii Wychowania, 2008)
The question of girl’s education was broadly discussed in the columns of women’s magazines. For the majority of women’s press editorial boards, there were two key issues which dominated in the articles. The first issue was connected with promotion, among women readers, of awareness that providing education for their daughters became necessary in order to compete with men on the job market. The second issue, in turn, concerned the condition of women’s educational system in Polish territories and the direction of development it should evolve in the face of new challenges posed before women in the Second Polish Republic.